2008
DOI: 10.1088/1742-6596/123/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

Power requirement for accessing the H-mode in ITER

Abstract: Abstract. The input power requirements for accessing H-mode at low density and maintaining it during the density ramp in ITER is addressed by statistical means applied to the international H-mode threshold power database. Following the recent addition of new data, the improvement of existing data and the improvement of selection criteria, a revised scaling law that describes the threshold power required to obtain an L-mode to H-mode transition is presented. Predictions for ITER give a threshold power of ~52MW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
613
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 432 publications
(649 citation statements)
references
References 24 publications
32
613
4
Order By: Relevance
“…This very narrow (5%) power range contrasts strongly with the much wider range, more than a factor of two, seen at 5.6 T. It is closer to that observed on DIII-D and AUG. Figure 17 shows normalized power P loss / e n S vs B T . As for [36]. The upper bound of I-mode powers increases strongly with B T ; we note that many of the discharges at > 5 T are limited by available heating power and that the upper line does not necessarily reflect an I-H threshold.…”
Section: Power Thresholds For L-i and I-h Transitionsmentioning
confidence: 78%
“…This very narrow (5%) power range contrasts strongly with the much wider range, more than a factor of two, seen at 5.6 T. It is closer to that observed on DIII-D and AUG. Figure 17 shows normalized power P loss / e n S vs B T . As for [36]. The upper bound of I-mode powers increases strongly with B T ; we note that many of the discharges at > 5 T are limited by available heating power and that the upper line does not necessarily reflect an I-H threshold.…”
Section: Power Thresholds For L-i and I-h Transitionsmentioning
confidence: 78%
“…6a show that there is a B dependence as well). The ratio of measured L-I and I-H threshold power to the widely used H-mode threshold power scaling P LH,scaling [29] is shown in Fig. 6b.…”
Section: Access To I-mode and H-modementioning
confidence: 99%
“…S 0.94 (MW), where n e is the central line-averaged electron density in 10 20 m −3 , B T is the magnetic field in T, and S is the plasma surface area in m 2 [4]. However, ongoing research from many devices found that other 'hidden variables' affect the L-H power threshold.…”
Section: 80mentioning
confidence: 99%